THE EFFECTIVENESS OF ULTRASONIC LITHOTRIPTOR COMPARED TO COMBINED ULTRASONIC AND PNEUMATIC LITHOTRIPTOR IN PERCUTANEOUS NEPHROLITHOTOMY (PCNL) SURGERY: A SYSTEMATIC REVIEW AND META-ANALYSIS - Suryatmana, Anggana; Soebadi, Doddy M.; Djojodimedjo, Tarmono (Indonesian Journal of Urology, 2021)
Objective: To evaluate the effectiveness of the ultrasonic lithotriptor compared to the combined ultrasonic-pneumatic lithotriptor in percutaneous nephrolithotomy (PCNL). Material & Methods: A systematic search was conducted focusing on studies evaluating nephrolithiasis patients who underwent PCNL using pneumatic, ultrasonic, ultrasonic-pneumatic, or laser lithotriptor. The search was conducted in the PUBMED and Science-direct databases from early to September 2020. Results: There were 406 journals in the initial search. On further selection, 3 randomized controlled trials (RCT) were obtained, with a total of 251 patients. The stone-free rate of three studies had low heterogeneity, I2=0% (P=0.34), so a fixed effect statistical model was used. There was no significant difference (P=0.44) between the stone-free rates from the ultrasonic lithotriptor group and the combination with an odds ratio of 1.26 (95% CI = 0.70-2.26). High heterogeneity was obtained with I2=71% (P=0.03) for the mean fragmentation time, so random effect statistical model was used. There was no significant difference (P=0.56) between the mean fragmentation time of the ultrasonic lithotriptor and combination group with a mean difference of -3.69 (95% CI = -16.09-8.71). Conclusion: The ultrasonic lithotriptor did not have a significant difference in stone-free rate, and mean fragmentation time compared to the combined ultrasonic-pneumatic lithotriptor in PCNL. More RCT studies are needed.